Effectiveness of COVID-19 vaccines: A systematic review - Paul Sony; Iyanar Kannan; Pitchai Rathinam Thenmozhivalli (Asian Journal of Medical Sciences, 2023)
COVID-19 vaccine effectiveness has been the subject of numerous investigations conducted globally. The public’s and health-care professionals’ acceptance of vaccines looks to be crucial to the pandemic’s effective management. This review’s objective was to present an up-to-date evaluation of COVID-19 vaccine acceptance rates across the globe. The current systematic evaluation of the literature seeks to identify the many global outcomes of the COVID-19 vaccine’s efficacy. The study was carried out following preferred reporting items for systematic reviews and meta-analysis recommendations for systematic reviews. The MEDLINE and EMBASE database were used the retrieve the articles. A detailed descriptive analysis was done on the various outcomes of vaccine efficacy, viral load, transmission rate, hospitalization rate, death rate, and infectivity rate on age group. The present systematic review has identified that vaccines effectively reduced infection transmission. It not only provides fewer hospital stays but reduced the death rate. However, the Ct values were similar in unvaccinated and vaccinated. Breakthrough infections were most reported in the vaccinated group.